Clinical characteristics and electroencephalography features of intractable childhood epilepsy - A case series - Irawan Mangunatmadja; Eva Devita Harmoniati (Indonesian Pediatric Society, 2010)
Background The majority of epilepsy patients have good prognosis,Â but lOAO% will develop intractable epilepsy. Early identificationÂ of patients v.ith risks of developing intractable epilepsy allowsÂ more intensive therapy to be performed.Objective To study clinical characteristics and electroencephalography (EEG) features of intractable childhood epilepsy.Methods We reviewed children lith intractable epilepsy attendingÂ the Pediatric Neurology and Growth and Development Clinic inÂ Child Health Department, Cipto Mangunkusumo Hospital fromÂ 2005ô€2008. EEG examination was perfonned in epilepsy patientsÂ who had consumed two or more antiepileptic drugs for at leastÂ 18 months but still experienced seizure at least once per month.Â Data of clinical characteristics were collected from the medicalÂ records and information provided by the parents.Results There were 41 subjects. Age of onset between oô€ 1 yearÂ old was found in 50% subjects, neurological impainnent in 80%,Â microcephaly in 50%, and abnonnalÂ neuroimaging in 14 of 24Â subjects. Seizure manifestations were mostly generalized tonicÂ clonic, tonic, my oclonic, and complex partial seizures. AbnonnalEEG features were found in 88% subjects and the majorityÂ showed generalized sloMng of the background activity. FocalÂ and multifocal epileptifonn activity was found in 31 % and 28%Â subjects, respectively. Epileptifonn activity was located mostly inÂ the frontal and temporal lobe.Conclusions Most patients Mth intractable epilepsy haveageÂ of onset before the age of 1 year. A substantialpoportionofÂ them have neurological impairment, microcephaly,abnonnalÂ neuroimaging, and abnormal EEG features. Seizure manifestationÂ ismostlygeneralized seizure. Epileptiform activity in intractableÂ childhood epilepsy is often found in the frontal and temporal lobe.Â